'Add info and stir': an institutional ethnographic scoping review of family care-givers' information work. Issue 3 (5th March 2020) - Dalmer, Nicole K.
Abstract: Family care-givers are increasingly expected to find, understand and use information to meet the complex needs of older adults in their care. A significant number of studies, however, continue to report that care-givers' information needs are unmet. Following Arksey and O'Malley's scoping review framework, I examined 72 articles for the range and extent of available research on the information work done by family care-givers of community-dwelling older adults living with dementia. To untangle the complex relationship between information and care, this scoping review maps out (a) the ways scholarly literature conceptualises the informational components of family care-givers' work and (b) the degree to which scholarly research acknowledges these components as work. An institutional ethnography inflection enhanced the scoping review framework, enabling the privileging of lived experiences, questioning of assumptions of language used, attending to authors' positioning and highlighting care-givers' information work made invisible throughout the processes of academic research.